EFFECTS OF PREDICT-OBSERVE-EXPLAIN INSTRUCTIONAL MODEL ON STUDENT’S COGNITIVE STYLES AND ACADEMIC ACHIEVEMENT IN BIOLOGY - Okah, Destiny (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
This study was designed to determine the Effects of Predict-Observe-Explain instructional model on student’s cognitive styles and academic achievement in biology. Two research questions guided this study. A quasi-experimental pre-test, post-test control group design was used for this study. The sample for the study was two hundred and eighty (280) biology students. Data for this study was collected using a Two-tier diagnostic multiple choice biology achievement test and Cognitive style scale. Their validity and their reliability indices were established using Kuder-richardson formula 21 and Cronbach alpha respectively. The findings of this study showcased that there was significant difference in achievement score between the experimental and control group in favor of the experimental group and secondly there was no significant difference in the academic achievement of  field-dependent and field-independent cognitive style students taught biology using POE model. The study concluded that the POE model enhanced students of both cognitive styles’ academic achievement in biology. This study recommends that biology teachers should make use of the POE model and that POE instructional model should be incorporated into the educational system by curriculum planners due to its effectiveness in bridging the gap between students of varying cognitive styles.